Footprints of an Earthquake: Experiences of Firat University Students' from Van - Oner, Ilknur (Elsevier Science Bv, 2013)
This paper has a two-fold importance by focusing on specific affected groups (university students) of a natural calamity, yet based in Elazig city which is 475 km distant to the epicentre of the disaster. Disasters and their possible affects have been recognized with different aspects. Previously, the main focus was on the epicentre of such disasters. However, recent appearances of mass disasters are bringing that into light the necessity of recognition of the equality of the strength of its effects on its core and further afield. There are arguments that can be opened and applied from these long distance social effects. Most ongoing discussions have focused on heavily populated, disaster vulnerable locations such as Istanbul. I have tried to indicate the equal importance of the vulnerability of small settlements and their social conditions and the necessity of analyzing solutions in pilot locations for their forthcoming burdens of future disasters. The point goes beyond the earliest questions such as whose disaster is it? Van has exemplified this point once again with this unwanted experience. Due to these earliest approaches, the definition of affected people has been limited with the appraisal of those near to the epicentre. However, a university student group who live in another location because of their education can also be equally affected through their Firat University is an important example. In terms of time variability, the disaster occurred just before exam week while students were in need of heavy concentration for their studies and attendances to their lectures and studies pre-exam period. Recognised methodological difficulties to conduct social studies immediately following a disasters inevitably focussed the study to those people affected in our vicinity. In our case, this group was our students. The study instantly evolved around the accumulated knowledge on disasters and the urgent necessities of these students by listening to and identifying their experiences. These were done with the attempt of seeking possible solutions to urgent situations of the students. Within the frame of above mentioned phases: A focused group study between the participants through the meeting of affected students (over 75 individuals), following in depth interviews and then a survey questionnaire which will be carried on for a further year by registering university students from Van in the 2011-2012 academic year at the Firat University, Elazig. The study reveals the experiences and possible solutions in the processes. Discussions of the findings have been carried on the basis of local, national and international level of comparisons and experiences. Findings revealed that students from Van have footprints of the quake in their lives, through the experiences of their relatives and their reflections on their student lives. They require recognition due to the adverse effects on their concentration, attendances to courses, sleeplessness, their sense of guilt, need of scholarship, accommodation or accommodation fees, etc. Most of them required socio-psychological guidance and counselling. There are local facilities for these social needs but there are urgent needs in terms of processes such as collaboration, organization and activation of these support structures. (C) 2013 The Authors. Published by Elsevier Ltd.
3rd World Conference on Psychology, Counselling and Guidance (WCPCG) -- MAY 09-12, 2012 -- Efes, TURKEY
Keywords: Van earthquake; students' experiences; post-disaster; Firat University; Turkey